2011
DOI: 10.1071/sr10185
|View full text |Cite
|
Sign up to set email alerts
|

Soil carbon dynamics under different cropping and pasture management in temperate Australia: Results of three long-term experiments

Abstract: In addition to its important influence on soil quality and therefore crop productivity, soil organic carbon (SOC) has also been identified as a possible C sink for sequestering atmospheric carbon dioxide. Limited data are available on the impact of management practices on the rate of SOC change in agricultural soils in Australia. In this paper, results of three long-term trials (13-25 years) located near Wagga Wagga in temperate Australia were used to assess C dynamics under different tillage and stubble manag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
47
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(53 citation statements)
references
References 30 publications
6
47
0
Order By: Relevance
“…Hulugalle et al (2011) suggested that N fertiliser inputs, depth of soil disturbance, annual temperatures, and winter rainfall were more closely related to carbon gains and losses than was time. Although some authors have claimed carbon sequestration rates of~2 Mg C ha -1 year -1 or more in the surface 0.3 m of semi-arid irrigated Vertosols, our results do not support this view but concur with most of the studies conducted in irrigated and dryland row-cropped farming systems under semi-arid conditions (Hulugalle 2000;Luo et al 2010;Sanderman et al 2010;Chan et al 2011;Powlson et al 2011;White 2012).…”
Section: Soil Carbon Storage and Sequestrationsupporting
confidence: 46%
See 1 more Smart Citation
“…Hulugalle et al (2011) suggested that N fertiliser inputs, depth of soil disturbance, annual temperatures, and winter rainfall were more closely related to carbon gains and losses than was time. Although some authors have claimed carbon sequestration rates of~2 Mg C ha -1 year -1 or more in the surface 0.3 m of semi-arid irrigated Vertosols, our results do not support this view but concur with most of the studies conducted in irrigated and dryland row-cropped farming systems under semi-arid conditions (Hulugalle 2000;Luo et al 2010;Sanderman et al 2010;Chan et al 2011;Powlson et al 2011;White 2012).…”
Section: Soil Carbon Storage and Sequestrationsupporting
confidence: 46%
“…Under semi-arid conditions, however, significant and sustained sequestration of carbon has been reported primarily for farming systems with perennial crops and pastures (Luo et al 2010;Sanderman et al 2010;Chan et al 2011;Powlson et al 2011). Although some benefits have been reported for conservation farming practices such as zero-tillage and crop rotation, carbon sequestration rates have generally been low and subject to variables such as water and nutrient availability, temperature, soil condition and type, and management (Luo et al 2010;Sanderman et al 2010;Chan et al 2011;Powlson et al 2011). Where relatively high values (~2 Mg C ha -1 year -1…”
Section: Introductionmentioning
confidence: 99%
“…no carbonate C). The annualised net rates of organic C accumulation in southern NSW have previously been reported as being very slow and often negative (Chan et al, 2011). However there were sequences of seasons where gains and losses of soil organic C were very different to the average long term trend.…”
Section: Introductionmentioning
confidence: 92%
“…Soil disturbance and stubble removal can each result in a loss of soil carbon (Rasmussen & Collins 1991;Dalal & Chan 2001;Chan et al 2011;Roper et al 2010Roper et al , 2013. However, there is little research that quantifies the impacts of a switch away from crop residue retention and no-till on surface residue cover and soil water content.…”
Section: Introductionmentioning
confidence: 99%